2020
DOI: 10.1016/j.kint.2020.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of natriuretic peptides is associated with protein energy wasting and activation of browning in white adipose tissue in chronic kidney disease

Abstract: P rotein-energy wasting (PEW) and cachexia, a severe form of PEW, are associated with poor survival in chronic kidney disease (CKD) and may occur in 20% to 80% of hemodialysis (HD) patients. 1,2 However, the mechanisms involved in uremic PEW are complex and remain poorly understood. PEW is different from malnutrition as it cannot be overcome by nutritional supplementation. 3 To date, there are few, if any, effective therapies to improve PEW associated with CKD. 4 Whether there is an increase in resting energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 48 publications
(65 reference statements)
0
18
0
Order By: Relevance
“…As described above, an important trigger of cachexia is the imbalance of anabolic and catabolic processes, especially in adipose tissue. Luce et al 75 attributed CKD‐associated energy wastage to browning activation due to the direct effects of the uremic environment on adipocytes, which was closely associated with the accumulation of NPs in adipose tissue. The authors found increased resting energy expenditure in a CKD mouse model, along with increased levels of ANP and UCP1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…As described above, an important trigger of cachexia is the imbalance of anabolic and catabolic processes, especially in adipose tissue. Luce et al 75 attributed CKD‐associated energy wastage to browning activation due to the direct effects of the uremic environment on adipocytes, which was closely associated with the accumulation of NPs in adipose tissue. The authors found increased resting energy expenditure in a CKD mouse model, along with increased levels of ANP and UCP1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…We also showed that fluid accumulation contributed to a loss in fat mass (beta = −0.35, p < 0.0001). The underlying mechanism of such association may potentially be explained by the experiment of Luce et al, who reported that natriuretic peptides activated lipolysis and browning of fat by increasing the synthesis of uncoupling protein 1 in mouse model [ 47 ]. Therefore, fluid overload, which was often accompanied by elevation of natriuretic peptides and hypoalbuminemia, may play a role in pathogenesis of protein energy wasting.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of NPs to NPR-A results in generation of cyclic guanosine monophosphate (cGMP) from guanosine triphosphate, which further activates protein kinase G (PKG) and mammalian target of rapamycin (mTOR) targeting cells to perform effect (Fig. 2 A) [ 5 , 112 , 113 ]. This atypical serin/threonine protein kinase, mTOR controls numerous cellular functions related to cell growth and homeostasis including protein synthesis, metabolism, survival, and proliferation [ 114 ].…”
Section: Sacubitril/valsartan (Entresto®) and Browningmentioning
confidence: 99%